Specificity Protein 1: A Protein With a Two-Sided Role in Ischemic Stroke - Yu, Qinyang; Liu, Wangyang; Chen, Zhuohui; Zhang, Mengqi (Frontiers in Cellular Neuroscience, 2021)
Stroke is one of the leading causes of death and disability worldwide. However, there is a lack of effective medications to speed up the recovery process. Ischemic stroke, as the result of cerebral infarction or cerebral artery narrowing, is accompanied by hemiplegia or impaired consciousness. There are many transcription factors involved in the development of this condition, whose alterations can influence or signal the prognostic outcomes of ischemic stroke. Among them, the augmented expression of specificity protein 1 (SP1) can participate in the progression of the disease by binding DNA to regulate the transcriptions of many genes. Different studies have provided different answers as to whether SP1 plays a positive or a negative role in ischemic stroke. On the one hand, SP1 can play a cytoprotective role as both an antioxidant and anti-apoptotic agent for neurons and glial cells. On the other hand, it can also damage neuronal cells by promoting inflammation and exacerbating brain edema. In this review, we highlight the roles of SP1 in ischemic stroke and shed light on the underlying mechanism.